The Correlation between Novice Psychopaths, Time Management, and False Feelings in Metacognition: The Mediating Role of Impulsive Behaviors - Hosseinimotlagh, Mariam; Rashidi, Hadi; Abolfazli, Fereshteh; Akbari, Anahita; yasaghi, Fatemeh (Shahroud Journal of Medical Sciences, 2024)
Background: Hyperactivity disorder has become an insoluble problem for psychologists and psychiatrists, parents, and teachers. This study aimed to explore how impulsive behaviors mediate the relationship between time management and false feelings in consciousness or metacognition in novice psychopaths. Methods: The current study is a descriptive-correlational research with a cross-sectional research design, utilizing structural equation modeling (SEM). The target population consists of all individuals who have sought treatment at psychological clinics in Tehran, with documented psychopathic disorders between July and December of 2023. The sample size included 198 individuals diagnosed with psychopathic disorder by expert psychologists within the past year. Participants were selected through purposive sampling. The research utilized the Barratt Impulsivity Scale (BIS), Time-Management Scale, and Metacognition Questionnaire-30 (MCQ-30) as measurement tools. Descriptive statistics were analyzed using SPSS version 27, while SmartPLS version 4 was used to examine path coefficients. A significant level was set at 0.05. Results: Based on the findings from the study, it was revealed that the long-term planning aspect had a notable negative impact on both impulsive behaviors (β=-0.516, P-value